Gel Permeation Chromatography of Heparins - Mulloy, Barbara; Johnson, Edward A (Thrombosis and Haemostasis, 1980)
Gel permeation chromatography of heparins using water as solvent has recently been used to obtain fractions for biological investigation. We find that heparin fractions obtained in this way are not, necessarily, differentiated simply on a molecular size basis as has been alleged. Correlations between biological activity and molecular size obtained using such fractions must therefore be treated with caution.
Keywords: Heparin fraction activities; Heparin gel chromatography